2006
DOI: 10.1080/09500340600674242
|View full text |Cite
|
Sign up to set email alerts
|

An optimal photon counting polarimeter

Abstract: We present experimental results on a method to perform polarimetry on ensembles of single photons. Our setup is based on a measurement method known to be optimal for estimating the state of two level systems. The setup has no moving parts and is sensitive to weak sources (emitting single photons) of light as it relies on photon counting and has potential applications in both classical polarization measurements and quantum communication scenarios. In our implementation, we are able to reconstruct the Stokes par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…It was further shown that when these reference vectors define a tetrahedron in the Poincare sphere, the characterization rate is optimized [31]. Hence, characterization of single photon polarization states requires only 4 projective measurements [35]. This is of particular importance when considering N-photon states, where the number of projective measurements grows as 4 N [36], in contrast to standard polarimetry that grows as 6 N .…”
Section: Polarization-entangled Photon-pairsmentioning
confidence: 99%
“…It was further shown that when these reference vectors define a tetrahedron in the Poincare sphere, the characterization rate is optimized [31]. Hence, characterization of single photon polarization states requires only 4 projective measurements [35]. This is of particular importance when considering N-photon states, where the number of projective measurements grows as 4 N [36], in contrast to standard polarimetry that grows as 6 N .…”
Section: Polarization-entangled Photon-pairsmentioning
confidence: 99%
“…[3] for the properties of the tetrahedron measurement, and Ref. [6] for its implementation for experimental tomography of photon polarization qubits. The tensor product of two tetrahedron SIC POMs,…”
Section: Group Covariant Sic Poms and Their Fiducial Statesmentioning
confidence: 99%
“…To simplify experimental procedures, the fibre is deployed underground in a loop configuration with both ends connected to the lab. The stability of the deployed fibre is tested by sending in light with fixed polarisation and monitoring the output state with a polarimeter [28]. To compensate for this slow drift of polarization state transmitted over fiber, a polarization controller based on Liquid Crystal Variable Retarders (LCVRs) is adequate.…”
Section: Methodsmentioning
confidence: 99%